ANALISIS PENDAPATAN KARYAWAN PENYADAP TETAP TANAMAN KARET (Havea brasiliensis Muell Erg) (Studi Kasus di Perkebunan Biting PT.J.A. WATTIE Kecamatan Limbangan Kabupaten Kendal) - Aji Pustotok; Dewi Hastuti; Rossi Prabowo (Universitas Wahid Hasyim, 2014)
Payment of the employee is influence by some factors, there are the difference of age, education level and working experience of employee. Those differences can cause difference income of employee. The purpose of this research are to know the components of income, the level of income, and to know the correlation between age, education level and working experience with the level income of permanent employees of rubber tapper. The sampling methode had been conducted by taking populations of permanent employees tapper in PT. J.A. Wattie Biting plantation for about 73 employees to be sample. Whereas the data collection methode had been taken by interview and quotation. The income component of permanent employees tapper are consist of basic salary, subsidy, and premium. The average of income that are gotten by them in every month in 2012 is Rp. 985.878,-. The income are consist of Rp. 904.500,- for basic salary, Rp. 6.003 for premium and Rp. 75.375,- for subsidy. Sectoral Minimum Wage of Kendal Regency (UMKS Kendal in 2012), the income that are accepted by permanent employees tapper in PT. J.A. Wattie Biting plantation have qualified, it is Rp. 904.500,-. Based on data analysis with double correlation and SPSS 16,00 have known that coefficient correlation between age and income show very weak correlation. Education to age show very weak correlation, while working experience to income show there are no correlation. To know correlation from three predicator had been conduct by multiple correlation calculation. The result of calculation show tarithmatic < rtable, from it can be conclused that H0 is accepted and H1 is refused. So there are no correlation among age of employees, education level and working experience of employees tapper to total income that accepted. Keywords : Revenue, Permanent Employes, Tappers, Rubber